From the Margins to the Spotlight: Harnessing Executive Coaching to Empower Diverse Leadership Excellence - Dwi Savandha, Septien; Amelia, Amelia; Dwi Putri Pramesti, Ginna Novarianti (Cakrawala Repositori IMWI, 2025)
The increasing emphasis on diversity in leadership requires effective strategies to empower underrepresented leaders. This research explores the role of executive coaching in addressing the unique challenges faced by diverse leaders. This research aims to examine the role of executive coaching as a strategy for empowering diverse leaders and identify the most effective training approaches to support them. Utilizing a qualitative research design, interviews were conducted with diverse leaders participating in the coaching program. These findings indicate that a tailored coaching approach can significantly enhance self-awareness, resilience, and leadership effectiveness. Participants emphasized the importance of culturally responsive coaching practices, which foster trust and engagement. The research also underscores the importance of integrating coaching into broader diversity and inclusion initiatives to promote a more supportive environment for diverse leaders. This research provides valuable insights for organizations seeking to develop effective coaching strategies that foster diverse leadership excellence. The implications of this study suggest that organizations integrate executive coaching into their diversity and inclusion strategies, ensuring that coaches possess cross-cultural competencies to maximize the impact of coaching. This research also makes a significant contribution to the inclusive leadership practice and literature.